Urban domestic water supply in developing countries - Bhattacharya ([S.l.] : CBS Publishers & Distributors, 1992)
1 introduction. 2 factors influencing domestic water use. 3 water and health. 4 water quality. 5 water quantity. 6 metering domestic water supply. 7 pricing domestic water supply. 8 community participation in urban water supply. 9 conclusions and recommendations.